Vitamin D levels are associated with epistaxis severity and bleeding duration in hereditary hemorrhagic telangiectasia. (April 2018) - Weber, Lauren Marissa; McDonald, Jamie; Whitehead, Kevin
Aim: To explore the association between vitamin D levels and mild versus severe epistaxis, as well as the overall epistaxis severity score (ESS) in patients with hereditary hemorrhagic telangiectasia.Patients & methods: A retrospective chart review of 198 patients was performed to explore the relationship between vitamin D levels and the ESS. Vitamin D levels were also compared with those with mild epistaxis to those with severe epistaxis.Results: A significant difference was found between patient's vitamin D levels and their associated ESS and duration of epistaxis. Patients with mild epistaxis had higher levels of vitamin D than patients with severe epistaxis.Conclusion: Vitamin D is associated with features of hereditary hemorrhagic telangiectasia including ESS, bleeding time and epistaxis severity.